Idosos residentes em áreas pobres: prevalência de depressão e uso de serviços básicos de saúde - Rodrigues, Maria Aparecida Pinheiro (2009)
Objective: To assess the use of primary care by elderly with chronic conditions in the South and Northeast regions of Brazil. Methods: Cross-sectional study of 2889 individuals with age from 65 years, with chronic health conditions, living in adjacencies of primary care unit in 41 cities of the regions South and Northeast of Brazil. Adjusted analyses of outcomes were achieved through the Poisson regression. Results: The prevalence of medical consultation in the last six months was 45% in the South and 46% in the Northeast. The prevalence of participation in group of educational activities in the last year was 16% in the South and 22% in the Northeast. In both regions, the use of services was higher in elderly people under the age of 80 years, poorly educated and living in areas of coverage of primary care unit with family health program (FHP). Only in the South the elderly with disability had higher prevalence of medical consultations. Conclusions: The prevalence of medical consultation and participation in educational activities were lower than estimated. The results indicate that, despite the FHP promote greater use of primary care unit for elderly people with chronic conditions that living in adjacencies, it is need to expand access of elderly over 80 and older with disability.